Physiological and biochemical responses to cold and drought in the rock-dwelling pulmonate snail, Chondrina avenacea - Koštál, Vladimír; Rozsypal, Jan; Pech, Pavel; Zahradníčková, Helena; Šimek, Petr (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2013)
The pulmonate snail Chondrina avenacea lives on exposed rock walls where it experiences drastic daily and seasonal fluctuations of abiotic conditions and food availability. We found that tolerance to dry conditions was maintained at a very high level throughout the year and was mainly based on the snails' ability to promptly enter into estivation (quiescence) whenever they experienced drying out of their environment. Snails rapidly suppressed their metabolism and minimized their water loss using discontinuous gas exchange pattern. The metabolic suppression probably included periods of tissue hypoxia and anaerobism as indicated by accumulation of typical end products of anaerobic metabolism: lactate, alanine and succinate. Though the drought-induced metabolic suppression was sufficient to stimulate moderate increase of supercooling capacity, the seasonally highest levels of supercooling capacity and the highest tolerance to subzero temperatures were tightly linked to hibernation (diapause). Hibernating snails did not survive freezing of their body fluids and instead relied on supercooling strategy which allowed them to survive when air temperatures dropped to as low as -21 °C. No accumulation of low-molecular weight compounds (potential cryoprotectants) was detected in hibernating snails except for small amounts of the end products of anaerobic metabolism.
Keywords: Seasons; zvířata; metabolomika; anaerobióza; Estivation; Acclimatization; Snails; letní spánek; hlemýždi; Environment; období sucha; Hibernation; spotřeba kyslíku; Cold Temperature; Animals; hibernace; Droughts; nízká teplota; životní prostředí; Anaerobiosis; Oxygen Consumption; aklimatizace; Metabolomics; roční období